In vitro antiplasmodial activity and prophylactic potentials of extract and fractions of Trema orientalis (Linn.) stem bark - John Oludele Olanlokun; Oluwole Moses David; Anthony Jide Afolayan (BMC, 2017)
Abstract Background Trema orientalis (T. orientalis Linn) has been used in the management of malaria in the western part of Nigeria and despite its application in ethnomedicine, there is dearth of scientific evidence to justify the acclaimed prophylactic antimalarial usage of the plant. The aim of this study is to assess the in vitro antiplasmodial cell-free assay and chemopreventive efficacy of the methanol extract of the stem bark of T. orientalis and its fractions as a prophylactic regimen for malaria prevention. Also, the antimicrobial activities of the extract and the fractions were investigated. Method Vacuum liquid chromatography was used to obtain dichloromethane, ethylacetate and methanol fractions from the methanol extract of T. orientalis. The fractions were tested for their prophylactic and cell-free antimalarial activity using murine models and β-hematin formation assay respectively. Disc diffusion method was used to determine the antibacterial activity of the extract and its fractions against both Gram-positive and Gram-negative bacteria. Results In the prophylactic experiment, dichloromethane (DCMF), methanol fraction (MF) and extract (ME) (in this order) showed significant chemopreventive effects against P. berghei invasion of the red blood cells when compared with both Sulfadoxine-Pyrimethamine (SP) and untreated controls. Results of the in vitro study showed that the DCMF had the highest effect in preventing the formation of β-hematin when compared with other fractions. The DCMF also had the highest percentage inhibition of β-hematin formation when compared with chloroquine. The extract and fractions showed a concentration dependent antibacterial activity. Methanol extract had a pronounced inhibitory effect on Enterobacter cloaca ATCC 13047 and Enterococcus faecalis ATCC 29212. Serratia mercescens ATCC 9986 and Pseudomonas aeruginosa ATCC 19582 were the most susceptible bacteria. Conclusion The results obtained showed that both extract and fractions of T. orientalis possessed antiplasmodial and antimicrobial activity.